Geochemical and isotopic evidences for a severe anthropogenic boron contamination: A case study from Castelluccio (Arezzo, central Italy). (December 2015) - Venturi, Stefania; Vaselli, Orlando; Tassi, Franco; Nisi, Barbara; Pennisi, Maddalena; Cabassi, Jacopo; Bicocchi, Gabriele; Rossato, Luca
Abstract: In 2009 a deterioration of garden plants watered with domestic wells was related to high boron concentrations (up to 57 mg/L) measured in the shallow aquifer from the industrial area of Castelluccio (Tuscany, Italy), where several factories are or were using boron compounds for their industrial processes. Since 2012 a geochemical and isotopic survey of stream, ground and waste waters, and sediment samples was performed. In addition, monthly geochemical surveys were carried out from January to September 2013, during which concentrations of boron up to 139 mg/L were measured. The geochemical dataset also included raw (borax and sodium boron-hydride) and anthropogenic materials (B-rich slags and muds stored in one of the local factories), the latter being, to the best of our knowledge, analyzed for the first time in this work for bulk and leachate boron concentration and isotopic ratios. The results highlighted that the high concentrations of boron found in the local shallow aquifer had unequivocally an anthropogenic source. It was suggested that prolonged interaction between industrial (presently stored at ground level or buried) by-products and waste and meteoric waters was likely the main process responsible of the groundwater contamination as supported by the analysis of the major solutes. The dispersion of the contaminant could not clearly be observed downward the shallow hydrogeological circuit. Consequently, the presence of other sources of boron in the industrial area of Castelluccio cannot be excluded. This would also explain the reason why no univocal results were obtained by the 11 B/ 10 B isotopic ratios measured in water, sediment and (bulk and leachate) anthropogenic samples. To minimize the boron contamination a hydraulic barrier should be constructed where the highest concentrations of boron were measured. Highlights: High boron concentrations were measured in a groundwater system near Arezzo (Italy). Several factories in the local industrial area were using B-rich products. Seasonal variations of B concentrations were observed during monthly monitoring. Boron isotopes were not conclusive for recognizing the contamination source(s). B contamination resulted by industrial activities via recent or ongoing spilling.